Mineral–Soil–Plant–Nutrient Synergisms of Enhanced Weathering for Agriculture: Short-Term Investigations Using Fast-Weathering Wollastonite Skarn - Jariwala, Hiral; Haque, Fatima; Vanderburgt, Stephen; Santos, Rafael M.; Chiang, Yi Wai (Frontiers in Plant Science, 2022)
Enhanced weathering is a proposed carbon dioxide removal (CDR) strategy to accelerate natural carbon sequestration in soils via the amendment of silicate rocks to agricultural soils. Among the suitable silicates (such as basalt and olivine), the fast-weathering mineral wollastonite (CaSiO3) stands out. Not only does the use of wollastonite lead to rapid pedogenic carbonate formation in soils, that can be readily detected for verification of carbon sequestration, but its weathering within weeks to months influences soil chemistry and plant growth within the same crop cycle of its application. This enables a variety of short-term experimental agronomic studies to be conducted to demonstrate in an accelerated manner what could take years to be observed with more abundant but slower weathering silicates. This paper presents the results of three studies that were conducted to investigate three distinct aspects of wollastonite skarn weathering in soils, in the context of both agricultural and horticultural plants. The first study investigates the effect of a wide range of wollastonite skarn dosages in soil (1.5 wt.%-10 wt.%) on the growth of green beans. The second study provides insights on the role of silicon (Si) release during silicate weathering on plant growth (soybeans and lettuce). The third study investigates the effect of wollastonite skarn on the growth of spring rye when added to soil alongside with a nitrogen-based coated fertilizer. The results of these three studies provide further evidence that amending soil with crushed silicate rocks leads to climate-smart farming, resulting in inorganic carbon sequestration, as well as better plant growth in agricultural (soybean and spring rye) and horticultural (green bean and lettuce) crops. They also demonstrate the value of working with wollastonite skarn as a fast-weathering silicate rock to accelerate our understanding of the mineral–soil–plant–nutrient synergism of enhanced weathering.